2020
DOI: 10.3390/medicina56120721
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Quality of Work Life in a Sample of Cancer Survivor Female Nurses

Abstract: Background and objectives: Identifying the factors affecting the Quality of Work Life (QWL) of cancer survivor female nurses is important and necessary to overcome the various challenges experienced by these professionals upon returning to work following recovery from the disease. Therefore, this study aimed to identify the factors affecting the level of nurses’ QWL. Materials and Methods: A cross-sectional survey was conducted among 115 registered female nurses who had survived cancer, in general hospitals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a recent study by Lyons et al [25], it was shown that more than two-thirds of women with MBC report being restricted in work and require a series of work-based adaptions indicating social support and understanding in the workplace are essential. It has been shown that greater social support, as well as lower job stress and fatigue, predicts a better quality of working life in cancer survivors [30,31]. It is plausible that our finding could be underpinned by greater experience of employers reducing levels of job stress, increasing work engagement and promoting a sense of value and worthiness in the workplace, subsequently improving perceptions of quality of working life.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a recent study by Lyons et al [25], it was shown that more than two-thirds of women with MBC report being restricted in work and require a series of work-based adaptions indicating social support and understanding in the workplace are essential. It has been shown that greater social support, as well as lower job stress and fatigue, predicts a better quality of working life in cancer survivors [30,31]. It is plausible that our finding could be underpinned by greater experience of employers reducing levels of job stress, increasing work engagement and promoting a sense of value and worthiness in the workplace, subsequently improving perceptions of quality of working life.…”
Section: Discussionmentioning
confidence: 63%
“…A recent qualitative study by Chapman et al [29] revealed that working women living with a history of primary breast cancer often experience a lack of understanding from their employers when it comes to fatigue and cognitive impairment. Factors such as social support, job stress and fatigue have been shown to significantly influence quality of working life amongst cancer survivors [30,31]. Quality of working life is defined as 'the experiences and perceptions of cancer survivors in their work life' [32].…”
Section: Introductionmentioning
confidence: 99%
“…Just 15% of the studies we collected focused on the positive relationship between well-being and intentional mindfulness (n=4), 21 , 36 , 43 , 69 nutrition and exercise (n=4), 8 , 12 , 14 , 15 and restorative sleep (n=3). 34 , 74 , 76 These studies add to the growing body of knowledge that lifestyle interventions can reduce compassion fatigue, stress, and burnout with yoga, prayer, meditation, a balanced diet (non-specific), and quality sleep.…”
Section: Resultsmentioning
confidence: 99%
“…However, there were several other sources that used various non-validated self-developed outcome measurement tools, including qualitative instruments. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Most studies used cross-sectional study design as well as descriptive correlational methods.…”
Section: Reviewing the Quality Of Literaturementioning
confidence: 99%
“…Just 15% of the studies we collected focused on the positive relationship between wellbeing and intentional mindfulness (n=4), 21,36,43,69 nutrition and exercise (n=4), 8,12,[14][15] and restorative sleep (n=3). 34,74,76 These studies add to the growing body of knowledge that lifestyle interventions can reduce compassion fatigue, stress, and burnout with yoga, prayer, meditation, a balanced diet (non-specific), and quality sleep.…”
Section: Intentional Mindfulnessmentioning
confidence: 99%